UPAYA PENINGKATAN STANDAR KOMPETENSI LULUSAN - Aulia Rahman (ADIBA : JOURNAL OF EDUCATION, 2022)
Graduate competency standards play a very important role in preparing the curriculum every year. Graduate competence is measured by the ability to think, behave and act or the skills of each student to assess his knowledge and skills. Graduate competency standards are often known among schools as the curriculum. The curriculum is a path that must be passed for every student, if a student cannot complete the curriculum in an education, he is not declared to have passed. Graduation is also marked with the award of a diploma from the school concerned. The curriculum as a teaching program in an education is required to be able to compete with technological sophistication every year, curriculum changes will continue to be carried out according to the times and according to the needs of the community.